Synthesis, Spectroscopic, and Thermal Investigations of Metal Complexes with Mefenamic Acid - Karolina Kafarska; Michał Gacki; Wojciech M. Wolf (Journal of Chemistry)
The novel metal complexes with empirical formulae M(mef)2·nH2O (where M = Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II); mef is the mefenamic ligand) were synthesized and characterized by elemental analysis, molar conductance, FTIR-spectroscopy, and thermal decomposition techniques. All IR spectra revealed absorption bands related to the asymmetric (νas) and symmetric (νs) vibrations of carboxylate group. The Nakamoto criteria clearly indicate that this group is bonded in a bidentate chelate mode. The thermal behavior of complexes was studied by TGA methods under non-isothermal condition in air. Upon heating, all compounds decompose progressively to metal oxides, which are the final products of pyrolysis. Cu(II), Zn(II), and Cd(II) complexes were also characterized by the coupled TG-FTIR technique, which finally proved the path and gaseous products of thermal decomposition. Additionally, the coupled TG-MS system was used to determine the principal volatile products of thermolysis and fragmentation processes of Mn(mef)2·3H2O and Co(mef)2·2H2O.